Consumers willingness to pay (WTP) of special tax for non-green vehicles towards environmental performance in Malaysia - Safian, Sharul Shahida Shakrein; Hamzah, Hanny Zurina (Elsevier, 2019)
The use of the green concept in the automotive industry as an energy-efficient transport innovation is still regarded as a new technology in Malaysia. It also has the potential to alleviate environmental issues in order to improve environmental performance in the automotive industry context. As such, the significance of green technology has become a growing concern, especially among developing countries. The purpose of this study is to determine consumers’ willingness to pay for green vehicles towards solving environmental issues in Malaysia. In order to achieve this, the consumers’ willingness to pay (WTP) and their preferences were examined using the contingent valuation method (CVM) as found in previous studies. Data was gathered using survey questionnaires which were distributed among 445 Malaysians so as to know their preferences in terms of green vehicles and green practices. The data was analysed using Economic Valuation Method. The result shows that Malaysians are willing to pay the price increase in road tax by 6.49% maximum level for non-green vehicles as well as all control variables included in the doubled-bounded case. On the other hand, for a single-bounded case, the maximum value is 7.91% which is higher as respondents were given single WTP amount for acceptance compared to the double-bounded case when the initial WTP was followed by another different amount.